The Effect of Catalyst Support on the Bimetallic Ni-Ag Hydrogenation Catalyst Activity - Tedi Hudaya; Nita Ardelia Jairus; Tatang Hernas Soerawidjaja (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
Hydrogenation is the addition reaction of hydrogen into double bounds molecules that are very important in chemical industry. Nickel, cheaper but less active than platinum and palladium, is widely used as a hydrogenation catalyst.  Non-fossil source of hydrogen can be derived from formic acid decomposition reaction aided by a silver catalyst. Although the activity of nickel and silver are normally less than noble metals, the combination with   appropriate support are expected to produce catalysts which can compete with the more expensive noble metals. The purpose of this research is to find out which support that gives the best hydrogenation activity in Ni-Ag bimetallic catalyst system. Support used in this research were TiO2, g-Al2O3, and activated C with mole ratio Ni:Ag varied as 2:1, 3:1, and 4:1. Hydrogenation experiments conducted using kemiri sunan (Reutealis trisperma) oil with formic acid as H source, using a supported catalyst for 5 hours. The experimental results showed that all synthesized catalysts had good and comparable activities, capable of lowering the iodine value by about 32%. Catalyst with TiO2 support gave the best activity, followed by activated C, and g-Al2O3.  Meanwhile, the metal loading that yielded the best result was Ni:Ag of 4:1 . Prolonged hydrogenation lasted for 10 hours did not cause further hydrogenation reaction.